Quality improvement collaborative for improving patient care delivery in Argentine public health sector intensive care units - Loudet, Cecilia Inés (2024)
Background: The demand for healthcare services during the COVID-19 pandemic was excessive for less-resourced settings, with intensive care units (ICUs) taking the heaviest toll.Objective: The aim was to achieve adequate personal protective equipment (PPE) use in 90% of patient encounters, to reach 90% compliance with objectives of patient flow (OPF) and to provide emotional support tools to 90% of healthcare workers (HCWs).Methods: We conducted a quasi-experimental study with an interrupted time-series design in 14 ICUs in Argentina. We randomly selected adult critically ill patients admitted from July 2020 to July 2021 and active HCWs in the same period. We implemented a quality improvement collaborative (QIC) with a baseline phase (BP) and an intervention phase (IP). The QIC included learning sessions, periods of action and improvement cycles (plan-do-study-act) virtually coached by experts via platform web-based activities. The main study outcomes encompassed the following elements: proper utilisation of PPE, compliance with nine specific OPF using daily goal sheets through direct observations and utilisation of a web-based tool for tracking emotional well-being among HCWs.Results: We collected 7341 observations of PPE use (977 in BP and 6364 in IP) with an improvement in adequate use from 58.4% to 71.9% (RR 1.2, 95% CI 1.17 to 1.29, p<0.001). We observed 7428 patient encounters to evaluate compliance with 9 OPF (879 in BP and 6549 in IP) with an improvement in compliance from 53.9% to 67% (RR 1.24, 95% CI 1.17 to 1.32, p<0.001). The results showed that HCWs did not use the support tool for self-mental health evaluation as much as expected.Conclusion: A QIC was effective in improving healthcare processes and adequate PPE use, even in the context of a pandemic, indicating the possibility of expanding QIC networks nationwide to improve overall healthcare delivery. The limited reception of emotional support tools requires further analyses.